2012
DOI: 10.1007/s13187-012-0407-3
|View full text |Cite
|
Sign up to set email alerts
|

“Balint Group” Meetings for Oncology Residents as a Tool to Improve Therapeutic Communication Skills and Reduce Burnout Level

Abstract: Medical training, particularly residency, may pose many challenges and may lead to burnout. Oncology training may be more stressful, given the prolonged exposure to death and dying. Balint group is an intervention method common in medical training, aimed at improving communication skills and strengthening doctor-patient relationships. We arranged for our oncology residents, guided by a senior oncologist and a clinical psychologist, to meet monthly for a discussion of personal cases from the residents' experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 6 publications
3
71
1
6
Order By: Relevance
“…Furthermore, a study conducted on the population of 17 Israeli doctors, found that Balint groups can reduce burnout and contribute to their personal accomplishment [7], and these results are consistent with our study. In the US, a study was carried out on 14 doctors and it showed that Balint participants had more developed psychological skills compared to Non-Balint participants [31].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, a study conducted on the population of 17 Israeli doctors, found that Balint groups can reduce burnout and contribute to their personal accomplishment [7], and these results are consistent with our study. In the US, a study was carried out on 14 doctors and it showed that Balint participants had more developed psychological skills compared to Non-Balint participants [31].…”
Section: Discussionsupporting
confidence: 92%
“…Since the burnout syndrome is highly prevalent among nonspecialists [7,45], some researchers investigated the differences between specialists and nonspecialists in relation thereto [46] and they found that nonspecialists are more prone to depersonalization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations